The Generation Effect in the production of false memories. - Martínez Miramontes, Marisol; Gomes, Carlos F. A.; Mojardín-Heráldez, Ambrocio; Milnitsky Stein, Llilian (Anales de Psicología / Annals of Psychology, 2012)
The Generation Effect (GE) is the effect of better recalling information that was created by us in comparison to information that was only read. False Memories (FM) refer to recalling information that did not happen or that happened in a different way. We may hypothesize that the GE can produce higher levels of FM, as both the GE and FM have been explained in terms of semantic processing. Nevertheless, some studies have shown that the GE improves memory without increasing FM. The aim of the present study was to explore the impact of the GE on True Memories (TM) and on FM, as well as its influence on the time of testing, the mere-testing effect, and confidence level. The results indicated the classical GE: increased rates of TM without increases in FM. The GE was not persistent across time, showing a decline of more than 50% in confidence level over time. In addition, repetition enhanced TM (mere-testing effect).